2009
DOI: 10.1057/imfsp.2009.3
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Market Business Cycles with Remittance Fluctuations

Abstract: This paper analyzes the implications of remittance fluctuations for various macroeconomic variables and sudden stops. The paper employs a quantitative two-sector model of a small open economy with financial frictions calibrated to Mexican and Turkish economies, two major recipients, whose remittance receipts feature opposite cyclical characteristics. We find that remittances dampen business cycles in Mexico, whereas they amplify the cycles in Turkey. Their quantitative effects in the long run, approximated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Despite the significance of the remittances for the Turkish economy, there are a handful of macro-level studies and only one micro-level study on their determinants. Among the macro studies, Sayan (2004), Sayan and Tekin-Koru (2010) and Durdu and Sayan (2010) show that remittance flows from Germany are procyclical with Turkey's output, suggesting that Turkish migrants in Germany do not remit for altruistic reasons. The findings of Alper and Neyapti (2006) and Aydas et al (2005) provide evidence that remittances are used for both consumption and investment, although in both studies investment is more dominant in the long term.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the significance of the remittances for the Turkish economy, there are a handful of macro-level studies and only one micro-level study on their determinants. Among the macro studies, Sayan (2004), Sayan and Tekin-Koru (2010) and Durdu and Sayan (2010) show that remittance flows from Germany are procyclical with Turkey's output, suggesting that Turkish migrants in Germany do not remit for altruistic reasons. The findings of Alper and Neyapti (2006) and Aydas et al (2005) provide evidence that remittances are used for both consumption and investment, although in both studies investment is more dominant in the long term.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors find more mixed results (Durdu and Sayan, 2010 ; Mughal and Ahmed, 2014 ; Vargas-Silva, 2008 ).…”
Section: Related Literaturementioning
confidence: 94%
“…However, "other studies have challenged these results and have reported that the investment-driven, procyclical tendency may be more prevalent (Giuliano & Ruiz-Arranz, 2009;Hoai & Thanwadee, 2015;Lueth & Ruiz-Arranz, 2008)". In addition, " Durdu and Sayan (2010) documented that, whereas countercyclical remittances lows can mitigate macroeconomic volatility, procyclical lows have the potential to deepen it and the behavior of remittances during episodes of high macroeconomic volatility during current account reversals and inancial crises, and their potential to stabilize consumption in response to income shocks, remain understudied in the literature". Thus, with inadequate practical literature "on the dynamic patterns of remittances", the researcher pose some questions.…”
Section: Literature Reviewmentioning
confidence: 99%